Soil Erosion Control Practices and Their Effect on Watershed Degradation Reduction in the Upper Citarum Watershed, West Java, Indonesia - Asikin Muchtar (PT FORMOSA CENDEKIA GLOBAL, 2026)
The Cisangkuy Sub-Watershed in the Upper Citarum Basin, West Java, Indonesia, has experienced increasing environmental degradation due to intensive agricultural activities, deforestation, and unsustainable land management on sloping areas. These conditions have accelerated soil erosion, sedimentation, declining soil fertility, and hydrological imbalance, threatening watershed sustainability and increasing downstream flood risks. This study aims to analyze the effect of soil erosion control practices on watershed degradation reduction in the Cisangkuy Sub-Watershed. The research employed a quantitative explanatory approach using a cross-sectional survey combined with field observations. Data were collected from 135 respondents consisting of farmers, land managers, and environmental stakeholders through structured questionnaires, erosion assessments, and land condition observations. The study examined terracing, vegetative conservation, agroforestry systems, contour farming, and check dam implementation as soil conservation practices. Data were analyzed using multiple linear regression supported by descriptive environmental analysis. The findings indicate that all conservation practices significantly contribute to watershed degradation reduction. Vegetative conservation and agroforestry systems showed the strongest influence on reducing surface runoff, improving soil stability, and increasing water infiltration capacity. Furthermore, community participation and environmental awareness strengthened conservation effectiveness. The study concludes that integrated soil conservation strategies are essential to support sustainable watershed management in the Cisangkuy Sub-Watershed.